THE EFFECT OF THE USE OF VIDEO-BASED LEARNING MEDIA LIGHT AND OPTICAL TOOLS ON THE IMPROVEMENT OF STUDENTS 'LEARNING OUTCOMES - M Y Simanullang; P R N Simanjuntak (ISER (Indonesian Science Education Research), 2021)
This study aims see the use of instructional video media on student learning outcomes in the subject of light and optical tools for junior high school students with a random sample of grade eight junior high school students and online methods. The object of this research was students learning outcomes. Data collection techniques used test techniques through the Google form application. Quantitative data analysis techniques used in the form of test scores for student cognitive learning outcomes. The Test Instrument contains 20 multiple choice questions. The results showed that the video media was suitable for use with the "good" category as a learning medium for students